2022
DOI: 10.3390/cells11162533
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Microenvironment Regulates Axon Diameters Visualized by Cryo-Electron Tomography

Abstract: Axonal varicosities or swellings are enlarged structures along axon shafts and profoundly affect action potential propagation and synaptic transmission. These structures, which are defined by morphology, are highly heterogeneous and often investigated concerning their roles in neuropathology, but why they are present in the normal brain remains unknown. Combining confocal microscopy and cryo-electron tomography (Cryo-ET) with in vivo and in vitro systems, we report that non-uniform mechanical interactions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…When neurons were cultured on grids with either 2 µm holes spaced 1 µm apart (R 2/1) or 1.2 µm holes spaced 20 µm (R 1.2/20) apart, swellings were spotted along the neurite (Figure 2). These swellings resembled the varicosities that have been reported in past studies (Ma et al, 2022, Fischer et al, 2018, Schrod et al, 2018. We noted that at both the neurite and cell body, membrane blebs, defined as spherical, blister-like membrane protrusions commonly seen in processes of apoptosis and cytotoxicity, were frequently seen surrounding the periphery, (Ponuwei, 2017, Lesort et al, 1997.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…When neurons were cultured on grids with either 2 µm holes spaced 1 µm apart (R 2/1) or 1.2 µm holes spaced 20 µm (R 1.2/20) apart, swellings were spotted along the neurite (Figure 2). These swellings resembled the varicosities that have been reported in past studies (Ma et al, 2022, Fischer et al, 2018, Schrod et al, 2018. We noted that at both the neurite and cell body, membrane blebs, defined as spherical, blister-like membrane protrusions commonly seen in processes of apoptosis and cytotoxicity, were frequently seen surrounding the periphery, (Ponuwei, 2017, Lesort et al, 1997.…”
Section: Resultssupporting
confidence: 84%
“…With the observation that chemically fixed Drosophila neurons had considerably better cellular integrity and reduced frequency of varicosities, we decided to quantitatively examine the nature of these varicosities. We defined varicosities as oblong-shaped swellings that have diameters at least three times larger than the flanking neurites, based on past work that examined these objects present in tomograms of mouse neurons (Ma et al, 2022). Such swellings can become as large as 6 µm, which can be easily resolved by light microscopy yet were rarely seen by FLM before plunge-freezing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies in other systems have suggested that varicosities can form directly from “stopped” growth cones ( Hatada et al, 1999 ), and that their distribution can be described by random point-processes such as the Poison process ( Hellwig et al, 1994 ). More recent studies have shown that varicosities strongly respond to their mechanical and biological environment ( Shepherd et al, 2002 ; Ma et al, 2022 ) and are generally plastic, including pathological states ( Gu, 2021 ). In the mouse brain, serotonergic axons appear to undergo a developmental transition from “dot-like” enlargements, with virtually undetectable connections, to a smooth morphology by the end of the first developmental month ( Maddaloni et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%